Integrasi Kearifan Lokal dalam Reboisasi Hutan Lindung Batukliang Utara - Isfana, Qaila; Ayuni, Firda; Iskandar, Junaidi (Journal of Community Development and Empowerment, 2025)
Reforestation of protected forests is a vital effort in maintaining environmental sustainability and preventing ecosystem degradation. This study aims to analyze the role of local wisdom in supporting reforestation programs in the North Batukliang Protected Forest area, Central Lombok Regency. The method used is a descriptive qualitative approach through field observations, in-depth interviews with traditional leaders, local communities, and relevant agencies, as well as document analysis. The results of the study show that the local community possesses traditional values that support forest conservation, such as the "pemali" system (customary prohibitions), local knowledge of endemic plant species, and the practice of mutual cooperation (gotong royong) in tree planting. The integration of local wisdom has proven to enhance community participation in reforestation activities and strengthen the sense of ownership towards the forest area. Moreover, this local wisdom-based approach also strengthens social relations among residents and creates a model for sustainable forest management. However, challenges remain in the form of economic pressures, land-use changes, and limited technical support from external parties. Therefore, synergy between the government, indigenous communities, and non-governmental organizations is necessary to formulate reforestation policies that acknowledge and maximize the potential of local wisdom. This study recommends the mainstreaming of local wisdom in environmental policy as a long-term forest conservation strategy.